2012
DOI: 10.1249/mss.0b013e31825abc7c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dehydration during Cycling on Skeletal Muscle Metabolism in Females

Abstract: Progressive dehydration significantly increased HR, Tc, RPE, Pvol loss, whole body CHO oxidation, and muscle glycogenolysis, and these changes were already apparent in the first hour of exercise when body mass losses were ≤ 1%. The increased muscle glycogenolysis with DEH appeared to be due to increased core and muscle temperature, secondary to less efficient movement of heat from the core to the periphery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 33 publications
2
57
0
1
Order By: Relevance
“…Only 2 players in the CES trial had a peak Tc greater than 39°C, compared with 8 players in NF. The 0.3°C difference in Tc is lower than the 0.5-0.6°C difference measured in studies of 2% dehydration during steady-state exercise in the laboratory (Logan-Sprenger et al 2012, 2013Baker et al 2007), but similar to the 0.4°C difference measured during a self-paced soccer game (Edwards et al 2007). During the same period that Tc was reaching its peak in the present study, players in the CES trial had increased skating speed and time at high effort.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Only 2 players in the CES trial had a peak Tc greater than 39°C, compared with 8 players in NF. The 0.3°C difference in Tc is lower than the 0.5-0.6°C difference measured in studies of 2% dehydration during steady-state exercise in the laboratory (Logan-Sprenger et al 2012, 2013Baker et al 2007), but similar to the 0.4°C difference measured during a self-paced soccer game (Edwards et al 2007). During the same period that Tc was reaching its peak in the present study, players in the CES trial had increased skating speed and time at high effort.…”
Section: Discussionsupporting
confidence: 46%
“…Sweat rates in CES and NF were similar, while Tc was lower in CES, suggesting that there was increased heat transfer from the core of the body to the periphery in CES. Logan-Sprenger et al (2012, 2013 reported lower Tc in both men and women while cycling in a temperate environment while staying hydrated with water versus progressive mild dehydration, even though sweat rates were identical. During exercise, the cardiovascular system must provide adequate blood flow to the contracting muscles to maintain the exercise intensity and to the skin for adequate heat dissipation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, water losses ≥ 2% of total body weight impair significantly exercise and skill performance (1, 5) both in laboratories and field studies as well as mental performance in hot environments (7, 27, 28). Moreover, recent studies indicated that even lower levels of dehydration (~ −1%) provoke unfavorable changes in the athletic performance (6, 18). …”
Section: Introductionmentioning
confidence: 99%
“…The reality in sport is that the majority of athletes only replace ∼50% of sweat losses during exercise leading to significant fluid deficits, and as a result experiences amplified physiological responses compared to when drinking enough fluid to replace sweat losses (Burke 1997; Krause and Rodrigues-Krause 2011; Logan-Sprenger et al. 2013a, 2013b). …”
Section: Introductionmentioning
confidence: 99%